Morphometric measurements for sexual dimorphism in the Campolina horse breed - Krebs, Lisia Castro; Santos, Marina Monteiro de Moraes; Siqueira, Maria Claudia; Araujo, Brennda Paula Gonçalves de; Oliveira, Leonardo Gomes; Feitosa, Fabiany Sousa Costa; Camargo, Gregório Miguel Ferreira de; Oliveira, Chiara Albano de Araújo; Costa, Raphael Bermal; Schultz, Erica Beatriz; Godoi, Fernanda Nascimento de (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to distinguish the sexual dimorphism of horses of the Campolina breed, by morphometric measurements, and to classify them according to sex, using discriminating functions. Two-hundred and fifteen horses were measured, and 39 morphometric measurements were evaluated. The analysis of covariance and the discriminant analysis were performed. Males were taller and showed a wider chest, a greater scapular-humeral angle, and a larger neck, both in length and circumference. Females had a larger heart girth, wider hips, and a greater opening of the coxal-ground and femorotibial angles. Regarding classification, circumference measurements (85.58%) were more accurate in sexual differentiation than the linear (83.26%) and angular (73.02%) ones. As to classification error, of the total animals measured, 10 to 20% of the females were categorized as males. In addition, 11 to 38% of the males were categorized as females. It can be concluded that of the 39 morphometric measurements evaluated, 22 are responsible for sexual dimorphism in the Campolina horse breed. Circumference and linear measurements provide a more assertive classification to determine sexual dimorphism. Angular measurements show greater classification errors regarding the gender of the horses.